Penerapan Algoritma Rought Set Untuk Memprediksi Jumlah Permintaan Produk - Utari, Suci (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Demand is a number of goods purchased or requested at a certain price and time. Demand is related to consumer desires for goods and services to be fulfilled. And trends Consumer demand for goods and services is unlimited. In everyday terms, demand is defined in absolute terms, namely the amount of goods needed. This way of thinking is based on the idea that humans have needs. For this need, the individual has a demand for goods, the more residents of a country, the greater the public's demand for goods. Rapid Miner is open source software. Rapid Miner is a solution for analyzing data mining, text mining and clustering analysis. Rapid Miner uses a variety of descriptive and predictive techniques to provide users with insights so they can make the best decisions.